La mémoire de la participation des Espagnols à la Résistance française : une construction difficile - Miguel Sans (Cahiers de Civilisation Espagnole Contemporaine)
France’s recognition of the Spanish exiles' participation in the Resistance has been a long and difficult conquest. They took part to it in political disunity ; the only party that as such committed itself to this struggle was the Communist Party of Spain : it created the Spanish National Union, to which only a minority of fighters from other organizations gave support in their own name. They were disallowed by their own organization. That division culminated in violence. The memory of the Spanish resistance is still impregnated with these polemics: every political family, and more particularly the anarchists and the communists, wants to make recognize its greater participation. The occultations or glorifications which these polemics entail can only give a fragmented and incomplete knowledge of this Resistance, and make the work of historians difficult.